Firm value and its antecedents: testing the interaction effect of dividend policy - Phengdrawan, Jonassen; Kalis, Maria Christiana Iman; Wendy, Wendy; Fitriana, Ana; Irdhayanti, Efa (SEAN Institute, 2024)
The firm value represents investors' expectations of management's success in managing the firm, thereby enhancing the prosperity of investors. Firm value is crucial as it can shape perspectives and influence investor decision-making when investing in a firm. This research questions the effect of capital structure, profitability, and firm size on firm value in firms listed on the HIDIV20 index. This research also tests the dividend policy variable as a moderator. The research population includes firms listed on the HIDIV20 index of Bursa Efek Indonesia during 2018-2022. The sampling process is conducted through purposive sampling. Data analysis uses Moderate Regression Analysis (MRA) with panel data. The outcomes of the research reveal that capital structure and profitability have a positive impact on firm value, whereas firm size has a negative impact on firm value. Furthermore, dividend policy can moderate and strengthen the aftermath of profitability on firm value. This interaction effect is not observed in the outcome of capital structure and firm size on firm value.